Confirmation of CHD7 as a cause of CHARGE association identified by mapping a balanced chromosome translocation in affected monozygotic twins. Issue 3 (23rd August 2005) - Johnson, D; Morrison, N; Grant, L; Turner, T; Fantes, J; Connor, J M; Murday, V
Abstract : Background: CHARGE syndrome has an estimated prevalence of 1/10 000. Most cases are sporadic which led to hypotheses of a non-genetic aetiology. However, there was also evidence for a genetic cause with reports of multiplex families with presumed autosomal dominant, possible autosomal recessive inheritance and concordant twin pairs. We identified a monozygotic twin pair with CHARGE syndrome and a de novo balanced chromosome rearrangement t(8;13)(q11.2;q22). Methods: Fluorescence in situ hybridisation was performed with BAC and PAC probes to characterise the translocation breakpoints. The breakpoint on chromosome 8 was further refined using 10 kb probes we designed and produced using sequence data for clone RP11 33I11, the Primer3 website, and a long range PCR kit. Results: BAC and PAC probe hybridisation redefined the breakpoints to 8q12.2 and 13q31.1. Probe RP11 33I11 spanned the breakpoint on chromosome 8. Using our 10 kb probes we demonstrated that the chromodomain gene CHD7 was disrupted by the translocation between exons 3 and 8. Discussion: Identifying that the translocation breakpoint in our patients occurred between exons 3 and 8 of CHD7 suggests that disruption of this gene is the cause of CHARGE syndrome in the twins and independently confirms the role of CHD7 in CHARGE syndrome.